Design and testing of a supercapacitor storage system for the flash recharge of electric buses. (15th May 2021) - Pugi, Luca; Alessandrini, Adriano; Barbieri, Riccardo; Berzi, Lorenzo; Pierini, Marco; Cignini, Fabio; Genovese, Antonino; Ortenzi, Fernando
This paper proposes a hybrid storage for urban transport systems in order to reduce recharge time and increase its life and reliability. Proposed system is applied to a pre-existing electric vehicle, introducing through proposed revamping procedure a methodology for a fast integration of proposed systems on different vehicles. Finally, the system is calibrated and tested showing how the proposed control layout really simplifies the vehicle commissioning.